PET-NECK: a multicentre randomised Phase III non-inferiority trial comparing a positron emission tomography–computerised tomography-guided watch-and-wait policy with planned neck dissection in the management of locally advanced (N2/N3) nodal metastases in patients with squamous cell head and neck cancer - Hisham Mehanna; Chris C McConkey; Joy K Rahman; Wai-Lup Wong; Alison F Smith; Chris Nutting; Andrew GJ Hartley; Peter Hall; Claire Hulme; Dharmesh K Patel; Sandra Ventorin von Zeidler; Max Robinson; et al. (Health Technology Assessment, 2017)
Background: Planned neck dissection (ND) after radical chemoradiotherapy (CRT) for locally advanced nodal metastases in patients with head and neck squamous cell carcinoma (HNSCC) remains controversial. Thirty per cent of ND specimens show histological evidence of tumour. Consequently, a significant proportion of clinicians still practise planned ND. Fludeoxyglucose positron emission tomography (PET)–computerised tomography (CT) scanning demonstrated high negative predictive values for persistent nodal disease, providing a possible alternative paradigm to ND. Evidence is sparse and drawn mainly from retrospective single-institution studies, illustrating the need for a prospective randomised controlled trial. Objectives: To determine the efficacy and cost-effectiveness of PET–CT-guided surveillance, compared with planned ND, in a multicentre, prospective, randomised setting. Design: A pragmatic randomised non-inferiority trial comparing PET–CT-guided watch-and-wait policy with the current planned ND policy in HNSCC patients with locally advanced nodal metastases and treated with radical CRT. Patients were randomised in a 1 : 1 ratio. Primary outcomes were overall survival (OS) and cost-effectiveness [incremental cost per incremental quality-adjusted life-year (QALY)]. Cost-effectiveness was assessed over the trial period using individual patient data, and over a lifetime horizon using a decision-analytic model. Secondary outcomes were recurrence in the neck, complication rates and quality of life. The recruitment of 560 patients was planned to detect non-inferior OS in the intervention arm with a 90% power and a type I error of 5%, with non-inferiority defined as having a hazard ratio (HR) of no higher than 1.50. An intention-to-treat analysis was performed by Cox’s proportional hazards model. Settings: Thirty-seven head and neck cancer-treating centres (43 NHS hospitals) throughout the UK. Participants: Patients with locally advanced nodal metastases of oropharynx, hypopharynx, larynx, oral or occult HNSCC receiving CRT and fit for ND were recruited. Intervention: Patients randomised to planned ND before or after CRT (control), or CRT followed by fludeoxyglucose PET–CT 10–12 weeks post CRT with ND only if PET–CT showed incomplete or equivocal response of nodal disease (intervention). Balanced by centre, planned ND timing, CRT schedule, disease site and the tumour, node, metastasis stage. Results: In total, 564 patients were recruited (ND arm, n = 282; and surveillance arm, n = 282; 17% N2a, 61% N2b, 18% N2c and 3% N3). Eighty-four per cent had oropharyngeal cancer. Seventy-five per cent of tested cases were p16 positive. The median time to follow-up was 36 months. The HR for OS was 0.92 [95% confidence interval (CI) 0.65 to 1.32], indicating non-inferiority. The upper limit of the non-inferiority HR margin of 1.50, which was informed by patient advisors to the project, lies at the 99.6 percentile of this estimate (p = 0.004). There were no differences in this result by p16 status. There were 54 NDs performed in the surveillance arm, with 22 surgical complications, and 221 NDs in the ND arm, with 85 complications. Quality-of-life scores were slightly better in the surveillance arm. Compared with planned ND, PET–CT surveillance produced an incremental net health benefit of 0.16 QALYs (95% CI 0.03 to 0.28 QALYs) over the trial period and 0.21 QALYs (95% CI –0.41 to 0.85 QALYs) over the modelled lifetime horizon. Limitations: Pragmatic randomised controlled trial with a 36-month median follow-up. Conclusions: PET–CT-guided active surveillance showed similar survival outcomes to ND but resulted in considerably fewer NDs, fewer complications and lower costs, supporting its use in routine practice. Future work: PET–CT surveillance is cost-effective in the short term, and long-term cost-effectiveness could be addressed in future work. Trial registration: Current Controlled Trials ISRCTN13735240. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 21, No. 17. See the NIHR Journals Library website for further project information.